Sasadu: Traditional Houses in Sahu Tribe Community Reviewed from the Philosophy of Jürgen Habermas - Nanuru, Ricardo Freedom (Manunggal Halim Jaya, 2022)
The research entitled Construction of Public Sphere of Sasadu Traditional Houses in Sahu Tribe Community Reviewed from the Philosophy of Jürgen Habermas is motivated by the views of Sahu tribe community on their traditional houses which, according to the writer, only focus on the cultural-customary-religious traditions. In fact, Sasadu can be interpreted more than that, which is as a public Sphere in which Sahu tribe community together with the public authorities can build rational communicative discourse to reach consensus on the social, economic and political problems faced in West Halmahera for the sake of prosperity in living together. This research aimed to construct the philosophical concept of Sasadu traditional houses in Sahu tribu community based on the public sphere point of view of Jürgen Habermas. This research was a library study supported by field studies through observations and interviews. The method of data analysis applied in this research was philosophical hermeneutics. After conducting a search in this research, the results obtained are that Sasadu in Sahu tribe community in West Halmahera can be categorized as a public sphere in which private people and public authorities gather to form a “public” for developing argumentative rational discourse which will later be agreed to become a joint decision as a society which leads to public opinion. Sasadu, thus becomes a mediator between the private sphere of Sahu tribe community and the sphere of public authority, where social control is built and the values of universality are guarded.